Ischemic Stroke in Pontine and Corona Radiata: Location Specific Impairment of Neural Network Investigated With Resting State fMRI - Jiang, Chunxiang; Yi, Li; Cai, Siqi; Zhang, Lijuan (Frontiers in Neurology, 2019)
Objective: This study aims to investigate the location-specific functional remodeling following ischemic stroke in pons and corona radiata. Methods: Thirty six subjects with first ever acute ischemic stroke in pons (PS, n = 15, aged 62.8±11.01 years) or corona radiate (CRS, n = 21, aged 59.33±13.84 years) as well as 30 age and sex matched healthy controls (HC, n = 30, aged 60 ± 6.43 years) were recruited. Structural magnetic resonance imaging (MRI) and resting state functional MRI were conducted for each subject. Regional homogeneity (ReHo) and degree centrality (DC) were calculated with voxel-based approach. Intergroup differences in ReHo and DC were explored using permutation test with threshold free cluster enhancement (PT TFCE, number of permutations = 1000, family-wise error rate (FWER) < 0.05). Results: ReHo and DC alterations were identified in distributed anatomies for both PS and CRS groups. DC mainly increased in bilateral anterior and posterior cingulate cortex (PCC), inferior frontal-orbital gyrus, and decreased in bilateral cuneus, calcarine and precuneus (PCU), while ReHo mainly decreased in precentral and the postcentral gyri, inferior parietal lobules, PCU, PCC, and the superior occipital gyrus. PS and CRS groups were not significantly different in ReHo or DC after PT TFCE correction (FWER >0.05). Conclusions: IS-induced functional remodeling is extensive and location specific, suggesting that IS is a disease of connectivity disruption in addition to a focal vascular failure. The altered network centrality may underpin the clinicotopographical profiles during the disease dynamic of IS. Approaches targeting neural pathway and functional connectivity may shed light on better disease characterization and management innovation of IS.